Superior processability of Antheraea mylitta silk with cryo-milling: performance in bone tissue regeneration - Parekh, Nimisha; Bijosh, C. K.; Kane, Kartiki; Panicker, Alaka; Nisal, Anuya; Wangikar, Pralhad; Agawane, Sachin (International Journal of Biological Macromolecules, 2022)
Non-mulberry silk polymers have a promising future in biomedical applications. However, the dissolution of nonmulberry silk fiber is a still challenge and this poor processability has limited the use of this material. Here, we report a unique protocol to process the Antheraea mylitta (AM) silk fiber. We have shown that the cryo-milling of silk fiber reduces the beta sheet content by more than 10% and results in an SF powder that completely dissolves in routine solvents like trifluoroacetic acid (TFA) within few hours to form highly concentrated solutions (\~20 wt %). Further, these solutions can be processed using conventional processing techniques such as electrospinning to form 3D scaffolds. Bombyx mori (BM) silk was used as a control sample in the study. In-vitro studies were also performed to monitor cell adhesion and proliferation and hMSCs differentiation into osteogenic lineage. Finally, the osteogenic potential of the scaffolds was also evaluated by a 4-week implantation study in rat calvarial model. The in-vitro and in-vivo results show that the processing techniques do not affect the biocompatibility of the material and the AM scaffolds support bone regeneration. Our results, thus, show that cryo-milling facilitates enhanced processability of non-mulberry silk and therefore expands its potential in biomedical applications.
Keywords: Bone tissue engineering; Calvarial defect; hMSCs; Non-mulberry silk fiber; Processing technique